PRE-GERMINATION TREATMENTS IN SEEDS OF Mimosa strobiliflora BURKART - BIONDI, Daniela; LEAL, Luciana (Scientia Agraria, 2008)
Mimosa strobiliflora is a brush from the Fabaceae (Mimosoideae) family, usually found in the rivers margins. It is considered an extinction threatened species mainly due to the alteration of its site, caused by Pinus spp plantations that progressively invade native vegetation areas throughout the State of Paraná. The objective of this research was to identify methods for breaking the dormancy of Mimosa strobiliflora. The seeds were subjected following treatments: T0 = control; T1 = immersion in environment temperature water (27 °C) for 24 h; T2 = immersion in environment temperature water (27 °C) for 48 h; T3 = immersion in hot water (80 ºC) during 1 h; T4 = immersion in hot water (80 ºC) for 24 hours; and T5 = immersion in hot water (80 ºC) for 48 h. A completely random design with 6 treatments, 5 replications and 50 seeds was used to compare the treatments. The percentage and emergence speed rate were analyzed. Among the treatments for breaking the dormancy stands out T3, T4, and T5.